68Ga‐labeling of internalizing RGD (iRGD) peptide functionalized with DOTAGA and NODAGA chelators. (26th January 2020) - Satpati, Drishty; Vats, Kusum; Sharma, Rohit; Sarma, Haladhar Dev; Dash, Ashutosh
Abstract : The dual interaction with integrins and neuropilin‐1 receptor is the peculiar feature of iRGD peptide. Hence, in the present study, two iRGD peptide analogs were synthesized with DOTAGA and NODAGA as bifunctional chelator and aminohexanoic acid as a spacer for radiometalation with 68 GaCl3 . Negatively charged 68 Ga‐DOTAGA‐iRGD and neutral 68 Ga‐NODAGA‐iRGD radiotracers were investigated through in vitro cell uptake studies and in vivo biodistribution studies. Significant internalization of radiotracers in murine melanoma B16F10 cells was observed during in vitro studies. During in vivo studies, tumor uptake was higher for neutral 68 Ga‐NODAGA‐iRGD, but 68 Ga‐DOTAGA‐iRGD exhibited better tumor‐to‐blood ratio due to faster blood clearance. High kidney uptake of the two radiotracers was the limitation, which needs to be resolved through modification either in the peptide backbone or spacer/chelator. Abstract :